The Effect of Independence and Integrity on Audit Quality: Is There A Moderating Role for E-Audit? - Diza Dianeke Budi Prabowo; Dwi Suhartini (Universitas Hayam Wuruk Perbanas, 2020)
The financial statements must be reliable and become a benchmark in considering an audit decision on the financial statements. In order for this to be achieved, independence and integrity is required in carrying out the audit process. E-Audit helps overcome challenges in the industrial revolution 4.0 and prevent fraud. This research aims of testing and analyzing the role of e-audit in moderating the impact of auditor independence and integrity on audit quality. The data was collected through a questionnaire distributed to auditors at Public Accounting Firms in Surabaya. There are 36 respondents involved. The data were analyzed using SmartPLS. The results showed that auditor independence positively effect audit quality, auditor integrity positively effect audit quality; e-audit does non moderate the effect of auditor independence on audit quality; ande-Audit negatively moderates the effect of auditor integrity on audit quality. The practical implication of this research is that when determining high audit quality, independent auditors should at least increase their independence and integrity so that the resulting audit reports are of high quality and can be a reference for decision makers.